Information technology (IT) based intervention among individuals with ASD (autism spectrum disorder): A review - Khan, Mohammad Shadab; Mohamadali, Noor Azizah; Maher, Zulfikar Ahmad; Nisa, Syed Qamrun; Shaikh, Humaiz; Shah, Asadullah (Institute of Electrical and Electronics Engineers Inc., 2020)
The aim of this article is to provide systematic analysis of studies using ICT (information and Communication Technology) tools as intervention. These tools are categorized into two categories: (a) assessment tools and (b) Intervention tools. This review gives a brief description about the technological features and the functionality related to it. The intervention tools assist in enhancing cognitive and social abilities of the individual with ASD. Here we try to identify the latest advancement by reviewing these related articles and recommend future direction of extended research work.